Peran Manajemen Pendidikan dalam Mewujudkan Sekolah Berkualitas - Fathurrahman Suryadi; Muhammad Habib Pasaribu; Aqbil Daffa Siahaan; Ahmad Sabri; Yusran Lubis (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Optimizing education management in schools is a strategic step to achieve superior education quality, where various aspects such as human resource development, utilization of facilities and infrastructure, and education supervision play an important role in creating a conducive learning environment and responsive to student needs. The purpose of this study is to examine more deeply the role of education management in realizing quality schools. The research method to be used in this study is a literature study approach, in which data and information will be collected from various academic sources, such as books, journals and relevant articles on education management and quality schools. The results of this study show that effective education management plays a key role in creating quality schools through key components such as human resources, facilities and infrastructure, finance and education supervision. Each of these components works synergistically to support optimal learning processes, although they often face challenges such as limited resources, resistance to change and lack of stakeholder support. Through collaborative strategies from various parties, including the government, community and parents, schools can overcome these obstacles. Optimizing education management complemented by educational supervision helps improve the professional quality of teachers, curriculum and school management, and builds a culture of continuous evaluation. This synergy results in schools that are qualified, adaptive and able to respond to the demands of today's education.